2013
DOI: 10.1039/c3an00381g
|View full text |Cite
|
Sign up to set email alerts
|

Minimising contributions from scattering in infrared spectra by means of an integrating sphere

Abstract: Mid-infrared spectra of biological matter such as tissues, or microbial and eukaryotic cells measured in a transmission-type optical setup frequently show strongly distorted line shapes which arise from mixing of absorption and scattering contributions. Scattering-associated distorted line shapes may considerably complicate the analysis and interpretation of the infrared spectra and large efforts have been made to understand the mechanisms of scattering in biological matter and to compensate for spectral alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…The characteristic carbonyl (C = O) stretching mode was found in range of 1731‐1740 cm −1 . In the typical range 2849‐2951 cm −1 the C‐H stretching modes are found . A significant difference in absorbance of the stretching vibration of methylene and methyl group was encountered in the spectra, as expected based on the different alkyl chain lengths of the substituents R, where PSMA shows the strongest peaks, followed by PBMA and PMMA.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The characteristic carbonyl (C = O) stretching mode was found in range of 1731‐1740 cm −1 . In the typical range 2849‐2951 cm −1 the C‐H stretching modes are found . A significant difference in absorbance of the stretching vibration of methylene and methyl group was encountered in the spectra, as expected based on the different alkyl chain lengths of the substituents R, where PSMA shows the strongest peaks, followed by PBMA and PMMA.…”
Section: Resultssupporting
confidence: 61%
“…The thickness of the spin‐coated layers was determined by ellipsometry as (950 ± 30) nm, (670 ± 27) nm, and (850 ± 20) nm for PMMA, PBMA, and PSMA, respectively. Furthermore, IR spectra were acquired to examine the composition of polymers on the surface and the positions of the absorption peaks were compared to those from literature . The spectrum of each polymer is displayed in Figure [PMMA, (a); PBMA (b); PSMA, (c)].…”
Section: Resultsmentioning
confidence: 99%
“…[55][56][57][58][59]. It demonstrates the wide variation of absorbance distribution and Mie scattering effects at microscopic levels and suggests experimental conditions that minimize these problems.…”
Section: Discussionmentioning
confidence: 99%
“…An ab initio approach to circumvent this problem has been proposed by R. Bhargava (private communication, 2011); but until this approach is implemented in IR microspectrometers, the approximate methods need to be employed. Recently, Dazzi et al [25] demonstrated that the use of an integration sphere for data acquisition can eliminate the problem, but this approach is not suitable for simultaneous detection of multiple pixels of data, using an array detector.…”
Section: Correction For R-mie Effects and Data Preprocessingmentioning
confidence: 99%